2019
DOI: 10.3390/ijms20153813
|View full text |Cite
|
Sign up to set email alerts
|

Glial Dysfunction in MeCP2 Deficiency Models: Implications for Rett Syndrome

Abstract: Rett syndrome (RTT) is a rare, X-linked neurodevelopmental disorder typically affecting females, resulting in a range of symptoms including autistic features, intellectual impairment, motor deterioration, and autonomic abnormalities. RTT is primarily caused by the genetic mutation of the Mecp2 gene. Initially considered a neuronal disease, recent research shows that glial dysfunction contributes to the RTT disease phenotype. In the following manuscript, we review the evidence regarding glial dysfunction and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 145 publications
4
25
0
Order By: Relevance
“…In the absence of obvious change in the MBP and without labelling with an astrocyte nuclear marker, it is not fully clear whether the astrocyte number or the GFAP production is reduced. Regardless, these data support prior studies, mainly in animal models, by suggesting an important role for glial dysfunction in human RTT brain [70‐73].…”
Section: Discussionsupporting
confidence: 87%
“…In the absence of obvious change in the MBP and without labelling with an astrocyte nuclear marker, it is not fully clear whether the astrocyte number or the GFAP production is reduced. Regardless, these data support prior studies, mainly in animal models, by suggesting an important role for glial dysfunction in human RTT brain [70‐73].…”
Section: Discussionsupporting
confidence: 87%
“…These represent interesting evidence for differential regulation of MECP2 isoforms between cell types in a sex-specific fashion and support DNA methylation as a prevalent mechanism for the differential regulation. Also, although MECP2 is expressed at much lower levels in astrocytes relative to neurons, it has been reported that MECP2 -null astrocytes negatively affect neurons in a non-cell-autonomous fashion ( 67 , 68 ). The mechanisms regulating MECP2 expression in astrocytes are likely to be relevant for RTT and warrant further research.…”
Section: Mechanistic Insights Into Differential Gene Regulation Of Mementioning
confidence: 99%
“…Kir4.1 is an inwardly rectifying potassium channel that is responsible for a majority of the astrocytic potassium buffering [81]. Astrocytes from MeCP2-deficient mice express low level of Kir4.1 and subsequent elevated levels of extracellular potassium concentration [82], suggesting a role for astrocytic MeCP2 in the regulation of neuronal excitability [82]. Due to their peri-synaptic location, astrocytes could drive the elevated release of glutamate detected in RTT [31,79] modulating functional gamma oscillations known to underlie cognitive behavior [83].…”
Section: Introductionmentioning
confidence: 99%